Deep Services Trade Agreements and their Effect on Trade and Value Added - Borchert, Ingo; Di Ubaldo, Mattia (World Bank, Washington, DC, 2021)
The majority of services trade is currently transacted under the terms of preferential trade agreements (PTAs) with increasingly ambitious provisions on crossborder trade and investment in services. This paper exploits novel and detailed information on the architecture and depth of services PTAs (the World Bank Deep Trade Agreements 2.0 database) to study which provisions, or policy configurations, characterise an effective agreement. The richness of policy information is crucial for being able to identify those aspects that matter most, namely an agreement's structure, its rules of origin for firms and natural persons, and provisions that ensure accountability. Ambitious provisions in these areas are associated with 15-65 percent higher bilateral trade, driven by regulation-intensive services. Services PTAs also lead to an increase in services value added sourced from PTA partners, through provisions that facilitate the exchange of capital and people. This finding sheds light on how services PTAs can affect the configuration of value chain trade.